Achievement of Basic Cognitive Competency in News Text - Ryan Hidayat; Dwi Setiawan; Nanda Saputra; Sumarwati Sumarwati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to analyze the achievement of basic competencies (BC) and evaluate Indonesian language learning for each basic competency. This study uses qualitative descriptions and quantitative data. The results showed that in class VIIIE there were five students who had not reached the KKM and 7.5% was in the low category, 62.5% was in the medium category, and 30% was in the high category. Class VIIIF there are three students who have not reached the KKM and 2.5% is in the low category, 50% is in the medium category, and 47.5% is in the high category.